2012
DOI: 10.7439/ijbar.v3i4.424
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Hospitalized Burn Patients in Rural Area

Abstract: Background: Burns represent one of the major health problems in India. Epidemiological study is the first step in planning preventive and management strategies. Objective: To study some of the important epidemiological factors in relation to burn cases at a tertiary care level teaching hospital in rural area. Methods: Present study was retrospective study of all burn injury cases admitted at tertiary care level teaching hospital situated in rural area. The information obtained was tabulated analyzed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 12 publications
8
14
0
Order By: Relevance
“…Similar findings have been observed in studies reported by Akther JM et al and Deshpande JD et al 3,4 High incidence of burns in this age group may be because this age group is generally more active age group and more commonly exposed to hazards both at work and at home. This age group also included newly married females who became victims of bride burning.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar findings have been observed in studies reported by Akther JM et al and Deshpande JD et al 3,4 High incidence of burns in this age group may be because this age group is generally more active age group and more commonly exposed to hazards both at work and at home. This age group also included newly married females who became victims of bride burning.…”
Section: Discussionsupporting
confidence: 90%
“…[2][3][4][5][6][7] Female predominance may be because in our country cooking is considered as the primary responsibility of females so they are more commonly exposed to fire than males. Indian females wear loose fitting clothes like Sari, dupatta which can catch fire easily.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations